Pieces of Silver. - Kwa, Dipita (Langaa RPCIG, 2010)
Rosi-Daniela Kouoh, a female Divisional Officer newly appointed to Njopongo, steps into office at a time when preparations for elections in the Riders Union sows panic in the hearts of the townís barons and a tragic road accident ignites feelings of vengeance and survival. In order to determine the root-cause of the rising tension and build a platform for lasting calm and justice, she gets two men out of police custody; Sadi, a loser and bitter father of an unborn child, and Esingi, a daring, retired streetboy and chauffeur to the powerful Lord Mayor and business tycoon. This is the thrilling.